MXene-based room-temperature high-sensitivity no2 gas sensor driven by plasmonic photothermal and preparation method thereof
By introducing Ti3C2Tx/TiO2/Au nanocomposite materials into Ti3C2Tx-based gas sensors and utilizing the plasmonic photothermal effect, the problems of slow detection sensitivity and slow response recovery speed of Ti3C2Tx-based gas sensors at room temperature were solved, achieving high sensitivity and fast response NO2 detection.
Patent Information
- Application Number
- CN202410047052.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-01-12
AI Technical Summary
Existing Ti3C2Tx-based gas sensors have limited detection sensitivity and slow response recovery at room temperature, and traditional enhancement strategies have failed to effectively address the problem of insufficient activation energy for surface reactions.
A Ti3C2Tx/TiO2/Au nanocomposite material with a heterogeneous structure is used as the sensing material. By applying an external 530nm wavelength light source, a plasmonic photothermal effect is generated, forming a local high-temperature hot spot, which reduces the activation energy between gas molecules and the sensing material and enhances the energy of the gas-sensitive reaction.
It achieves high sensitivity detection, excellent selectivity and fast response/recovery rate for NO2 at room temperature, thus improving the overall gas sensing performance of the gas sensor.
Smart Images

Figure CN117929284B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of NO2 gas sensor technology, and more specifically to a plasmonic photothermal driven MXene-based room temperature high-sensitivity NO2 gas sensor and its preparation method. Background Technology
[0002] With the rapid development of the Internet of Things (IoT), room-temperature operating gas sensing modules that mimic or even replace human olfaction are attracting increasing attention, showing great application potential in various fields such as indoor and outdoor air quality monitoring, industrial and agricultural production, and medical diagnosis. Traditional metal-oxide-semiconductor (MOS) gas sensors rely on high-temperature heating, which increases power consumption and hinders compatibility with semiconductor processes, posing a significant challenge to gas sensor applications. Therefore, to meet the new requirements of emerging application scenarios for gas sensors, developing low-power devices that can operate at room temperature is crucial for practical sensing applications.
[0003] In recent years, two-dimensional transition metal carbides / nitrides (MXenes) have attracted widespread attention due to their unique physicochemical properties, especially a novel Ti3C2T... x Ti3C2T shows great promise in developing next-generation room-temperature gas-sensitive devices. However, the insufficient activation energy of the surface reaction hinders the realization of Ti3C2T operating at relatively low temperatures. x This poses a significant challenge for gas sensors, hindering their ability to detect subtle signal changes and resulting in limited detection sensitivity and slow response recovery.
[0004] Traditional sensitization strategies are based on Ti3C2T x Second-phase particles are introduced into the material to increase the number of active reaction sites in the sensitive material system, thereby effectively improving the efficiency of Ti3C2T. x This method improves the gas-sensing response capability of gas sensors, but it cannot fundamentally solve the problem of insufficient activation energy in gas-sensing reactions at room temperature.
[0005] Therefore, it is necessary to develop an effective and universal method to improve Ti3C2T x The comprehensive gas-sensing performance of the basic gas sensor at room temperature is of great significance for its practical application in the Internet of Things (IoT) field. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor and its fabrication method. This gas sensor utilizes a Ti3C2T heterostructure. xThe / TiO2 / Au nanocomposite material is used as the sensitive material. When excited by an external light source, a plasmonic photothermal effect is generated on the surface of the sensitive material, forming a local high-temperature hot spot. Driven by the local high-temperature hot spot, the gas sensor can achieve high sensitivity detection of NO2, excellent selectivity and fast response / recovery rate under room temperature operating conditions.
[0007] According to a first aspect of the present invention, a plasmonic photothermal driven MXene-based room temperature high-sensitivity NO2 gas sensor is provided, comprising a gas sensor composed of an Al2O3 substrate having multiple interdigitations and a sensitive material on the interdigitated electrodes, and a light source disposed above the gas sensor for emitting light in the 530nm wavelength range toward the gas sensor during detection, thereby providing a photo-assisted excitation environment.
[0008] The sensitive material is Ti3C2T with a heterostructure. x The / TiO2 / Au nanocomposite material generates a plasmonic photothermal effect in the sensitive material system through excitation by an external light source, which reduces the activation energy of the system reaction between the target gas molecules and the sensitive material. At the same time, the formed local high-temperature hot spots provide sufficient energy for the gas-sensitive reaction at room temperature, thereby enhancing the overall gas-sensitive performance of the gas sensor under room temperature operating conditions.
[0009] In an optional implementation, Ti3C2T x / TiO2 / Au nanocomposites include Ti3C2T exhibiting a multilayered structure. x And the lamellar TiO2 grown on its surface constitutes Ti3C2T with a heterostructure. x / TiO2 composite material, in the Ti3C2T x Au nanoparticles are freely distributed on the surface and / or edges of the TiO2 composite material, and the Au nanoparticles are related to Ti3C2T x The contact interface of the / TiO2 composite material forms a heterojunction.
[0010] In an optional embodiment, the average size of the Au nanoparticles is 30–35 nm.
[0011] According to a second aspect of the present invention, a method for fabricating the aforementioned plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor is provided, comprising the following steps:
[0012] Preparation of Ti3C2T x The prepared Ti3C2T x It exhibits a multi-layered structure;
[0013] In Ti3C2T xTi3C2T with a heterostructure is obtained by growing lamellar TiO2 on the surface. x / TiO2 composite material;
[0014] Au nanoparticles were loaded onto Ti3C2T x Au nanoparticles on TiO2 and Ti3C2T x The contact interface of the TiO2 composite material forms a heterojunction, resulting in Ti3C2T with a heterostructure. x / TiO2 / Au nanocomposite materials;
[0015] With heterostructure Ti3C2T x The preparation of gas sensors using TiO2 / Au as the sensing material specifically includes: using Ti3C2T x TiO2 / Au powder was dispersed in anhydrous ethanol to prepare a dispersion, which was then drop-coated onto an Al2O3 substrate with multiple interdigitated electrodes. After drying, a sensitive film was formed on the interdigitated electrodes, thus preparing a Ti3C2T electrode. x / TiO2 / Au as a gas sensor with sensitive material;
[0016] A light source is placed above the gas sensor to emit light in the 530nm wavelength range towards the gas sensor during detection. The excitation of the external light source causes a plasmonic photothermal effect on the surface of the sensitive material, which reduces the activation energy of the surface reaction between the target gas molecules and the sensitive material. At the same time, the formed local high-temperature hot spot provides sufficient energy for the gas-sensitive reaction at room temperature, thereby enhancing the overall gas-sensitive performance of the gas sensor under room temperature operating conditions.
[0017] In an optional implementation, Ti3C2T x The preparation process includes:
[0018] Step 1-1: Mix Ti3AlC2 powder with a mixture of LiF and HCl, and stir in a temperature-controlled water bath at 40°C for 48 hours.
[0019] Step 1-2: Use dilute hydrochloric acid to centrifuge the mixture from Step 1-1 several times to wash away any unreacted LiF.
[0020] Steps 1-3: Centrifuge the centrifuged product from Step 1-2 multiple times with deionized water with a resistivity greater than 18.2 MΩ·cm to eliminate residual LiF.
[0021] Steps 1-4: Wash and collect the precipitate obtained in steps 1-3, and vacuum dry it to obtain Ti3C2T with a multi-layered structure. x .
[0022] In an optional implementation, the heterostructure of Ti3C2T xThe preparation process of TiO2 includes:
[0023] Step 2-1: Prepare the Ti3C2T x Add it to the HCl solution, and add NaBF4 as a crystal facet control agent. Stir to make the solution evenly dispersed.
[0024] Step 2-2: Transfer the mixture from Step 2-1 to a polytetrafluoroethylene hydrothermal reactor and oxidize it at 160°C for 3 hours.
[0025] Step 2-3: Cool the product from Step 2-2, then wash the precipitate 3-5 times with deionized water and anhydrous ethanol. Collect the precipitate by centrifugation and vacuum dry to obtain Ti3C2T with a heterostructure. x / TiO2.
[0026] In an optional implementation, the heterostructure of Ti3C2T x The preparation process of / TiO2 / Au nanocomposite materials includes:
[0027] Step 3-1: The prepared Ti3C2T x / TiO2 and deionized water are added to a beaker and continuously oscillated in an ultrasonic instrument until they are evenly dispersed;
[0028] Step 3-2: Add HAuCl4·3H2O to the mixture obtained in Step 3-1 and stir at 25°C for 4 hours;
[0029] Step 3-3: Centrifuge the solution obtained in Step 3-2 alternately with deionized water and anhydrous ethanol 3-5 times, then vacuum dry the precipitate to obtain Ti3C2T. x / TiO2 / Au composite material.
[0030] In an optional implementation, the Ti3C2T x / TiO2 / Au exhibits a multi-layered structure with sheet-like TiO2 grown on its surface and Au nanoparticles freely distributed on the material surface and / or edges, forming a heterojunction at the material contact surface; the average size of the Au nanoparticles is 30-35 nm.
[0031] In an optional embodiment, the interdigitated electrode is an Ag-Pd electrode, the substrate material is Al2O3, the linewidth is 0.2 mm, and the spacing is 0.2 mm.
[0032] In an optional embodiment, the final sensitive membrane is formed by repeating the drop-coating and drying process 3 to 5 times during the preparation of the sensitive membrane.
[0033] As can be seen from the above technical solution of the present invention, the present invention utilizes in-situ grown composite Ti3C2T xA plasmonic photothermal driven MXene-based high-sensitivity NO2 gas sensor based on a TiO2 / Au heterostructure was successfully fabricated. Under specific visible light-assisted conditions, Au nanoparticles acted as light-absorbing nanoheaters, enhancing the plasmonic photothermal effect of the composite material system. This increased the temperature within the nanoscale range and the overall temperature of the material system, providing sufficient energy for the gas-sensitive reaction. The optimized Ti3C2T... x The / TiO2 / Au heterostructure gas sensor exhibits superior comprehensive gas sensing performance, including excellent NO2 sensitivity, fast response / recovery rate, excellent selectivity, reliable moisture resistance, and stability.
[0034] The plasmonic photothermal driven MXene-based room temperature high-sensitivity NO2 gas sensor proposed in this invention is a 530nm visible light assisted gas sensor. Furthermore, tests on various wavelengths of light have shown that it can achieve ultra-high sensitivity and fast response recovery speed for NO2 under 530nm visible light irradiation.
[0035] The present invention provides a 530nm light-assisted composite Ti3C2T x The plasmonic photothermal effect of the / TiO2 / Au heterostructure sensitive material system not only reduces the activation energy of the system reaction between the target gas molecules and the sensitive material, but also provides sufficient energy to accelerate the gas-sensing reaction process by increasing the local temperature around the active site, ultimately helping to enhance the overall gas-sensing performance of MXene-based sensors under room temperature operating conditions. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of the structure of the plasmonic photothermal driven MXene-based high-sensitivity NO2 gas sensor at room temperature according to the present invention.
[0037] Figure 2 This invention is used to prepare Ti3C2T x A schematic diagram of the process of creating the / TiO2 / Au composite material.
[0038] Figure 3 These are the XRD patterns of MT0, MT3, and MTA in the example of this invention.
[0039] Figure 4 These are the FE-SEM images of MT3 and MT0 in the example of this invention; where a is MT3 and b is MT0.
[0040] Figure 5 This is the FE-SEM image of the MTA in the example of this invention.
[0041] Figure 6 This is a particle size distribution diagram of Au nanoparticles in MTA in the example of this invention.
[0042] Figure 7 This is the EDS elemental spectrum of Ti, O, C, and Au of MTA in the example of this invention.
[0043] Figure 8 This is a TEM image of the MTA in the example of this invention.
[0044] Figure 9 This refers to the XPS spectrum measurement of MT3 and MTA in the example of this invention.
[0045] Figure 10 These are high-resolution XPS spectra of Ti 2p for MT3 and MTA in the example of this invention.
[0046] Figure 11 These are high-resolution XPS spectra of O1s for MT3 and MTA in the example of this invention.
[0047] Figure 12 These are high-resolution XPS spectra of C1s for MT3 and MTA in the example of this invention.
[0048] Figure 13 This is a high-resolution XPS spectrum of Au 4f of MTA in the example of this invention.
[0049] Figure 14 These are the UV-Vis absorption spectra of MT3 and MTA in the examples of this invention.
[0050] Figure 15 This is the dynamic response curve of the MT3 sensor in this invention to 1-50ppm NO2 over time.
[0051] Figure 16 The figures show the response / recovery curves of the MT3 sensor in this invention to 5ppm NO2 under different illumination conditions (i.e., no light, 365nm, 420nm, 495nm, 530nm and 620nm), with the inset showing a dot plot of the response values.
[0052] Figure 17 The MTA sensor in this invention provides the dynamic response / recovery curves of 1ppm NO2 under different illumination conditions (i.e., no light, 365nm, 420nm, 495nm, 530nm, and 620nm).
[0053] Figure 18 This is the dynamic response / recovery curve of the MTA-530 sensor in this invention to 1-50ppm NO2.
[0054] Figure 19This is the correspondence between the response values of the MT3, MTA, and MTA-530 sensors and the NO2 concentration in the examples of this invention.
[0055] Figure 20 This is a histogram comparing the selectivity of the MT3, MTA, and MTA-530 sensors of Embodiment 1 of the present invention for different gases.
[0056] Figure 21 This is a radar graph of each gas-sensing performance parameter of the MT3, MTA, and MTA-530 sensors for NO2 in the examples of this invention.
[0057] Figure 22 This is a graph showing the moisture resistance and long-term stability analysis of the MTA in the example of this invention.
[0058] Figure 23 This is a normalized electric field diagram on MT3 and MTA in the example of this invention.
[0059] Figure 24 These are infrared thermal images of MT3 and MTA in the example of this invention, taken at 200s intervals before and after 530nm light irradiation.
[0060] Figure 25 and Figure 26 These are schematic diagrams illustrating the NO2 sensing mechanism of the MTA-530 gas sensor in this invention under conditions of no light irradiation and with 530nm light irradiation. Detailed Implementation
[0061] To better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.
[0062] Various aspects of the invention are described in this disclosure with reference to the accompanying drawings, in which numerous illustrative embodiments are shown. The embodiments of this disclosure are not necessarily intended to encompass all aspects of the invention. It should be understood that the various concepts and embodiments described above, as well as those described below in more detail, can be implemented in any of a number of ways.
[0063] In recent years, novel two-dimensional transition metal carbon / nitrogen compounds (MXenes) have attracted great attention due to their unique physical, chemical, and electrical properties. Ti3C2T, as the first discovered MXene material,... x Rapid progress has been made in the field of gas detection. However, the problem of insufficient activation energy for surface reactions remains, especially for Ti3C2T operating at relatively low temperatures. x This poses a significant challenge for gas sensors, hindering their ability to detect subtle signal changes and resulting in limited detection sensitivity and slow response recovery.
[0064] Currently, the common method is in Ti3C2T x Second-phase particles are introduced into the material to increase the number of active reaction sites in the sensitive material system, thereby effectively improving the efficiency of Ti3C2T. x While gas sensors can improve gas-sensing response capabilities, they cannot fundamentally solve the activation energy problem in gas-sensing reactions, especially when operating at room temperature.
[0065] Therefore, this invention provides a plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor and its preparation method, using Ti3C2T with a heterostructure. x A gas sensor was prepared by using a TiO2 / Au nanocomposite material as the sensing material and then dropwise coating the prepared suspension onto the interdigitated electrodes to form a sensitive layer. A light source with a center wavelength of 530 nm was placed above the gas sensor.
[0066] The excitation of an external light source causes a plasmonic photothermal effect on the surface of the sensitive material, thereby forming a local high-temperature hot spot. Driven by the local high-temperature hot spot, the gas sensor can achieve high sensitivity detection of NO2, excellent selectivity and fast response / recovery rate under room temperature operating conditions.
[0067] Plasmon-driven photothermal MXene-based room-temperature high-sensitivity NO2 gas sensor
[0068] Combination Figure 1 As shown, in an exemplary embodiment of the present invention, a plasmonic photothermal driven MXene-based room temperature high-sensitivity NO2 gas sensor is provided, comprising a gas sensor composed of an Al2O3 substrate with multiple interdigitates and a sensitive material 2 on the interdigitated electrode 1, and a light source 3 is provided above the gas sensor to emit light in the wavelength range of 530nm towards the gas sensor during detection, providing a light-assisted excitation environment.
[0069] Among them, the sensitive material 2 is Ti3C2T with a heterostructure. x The / TiO2 / Au nanocomposite material generates a plasmonic photothermal effect in the sensitive material system through excitation by an external light source, which reduces the activation energy of the system reaction between the target gas molecules and the sensitive material. At the same time, the formed local high-temperature hot spots provide sufficient energy for the gas-sensitive reaction at room temperature, thereby enhancing the overall gas-sensitive performance of the gas sensor under room temperature operating conditions.
[0070] In an optional implementation, Ti3C2T x / TiO2 / Au nanocomposites include Ti3C2T exhibiting a multilayered structure. x And the lamellar TiO2 grown on its surface constitutes Ti3C2T with a heterostructure. x / TiO2 composite material, in the Ti3C2T xAu nanoparticles 21 are freely distributed on the surface and / or edges of the TiO2 composite material. Au nanoparticles 21 interact with Ti3C2T... x The contact interface of the / TiO2 composite material forms a heterojunction.
[0071] In an optional implementation, the multi-layered Ti3C2T x The dimensions are 500nm*500nm*50nm, and the multi-layered structure is a layered structure like an accordion.
[0072] In an optional embodiment, the size of the sheet-like TiO2 is 200nm*200nm*45nm.
[0073] In an optional embodiment, the average size of the Au nanoparticles is 30–35 nm.
[0074] Fabrication method of plasmonic photothermal driven MXene-based room temperature high-sensitivity NO2 gas sensor
[0075] In another exemplary embodiment of the present invention, a method for fabricating the aforementioned plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor is also provided, comprising the following steps:
[0076] Ti3C2T was prepared using a mild etching method. x The prepared Ti3C2T x It exhibits a multi-layered structure;
[0077] In-situ oxidation method was used in Ti3C2T x Ti3C2T with a heterostructure is obtained by growing lamellar TiO2 on the surface. x / TiO2 composite material;
[0078] Au nanoparticles were fabricated in Ti3C2T using an in-situ self-reduction method. x Loading Au nanoparticles on TiO2 with Ti3C2T x The contact interface of the TiO2 composite material forms a heterojunction, resulting in Ti3C2T with a heterostructure. x / TiO2 / Au nanocomposite materials;
[0079] With heterostructure Ti3C2T x The preparation of gas sensors using TiO2 / Au as the sensing material specifically includes: using Ti3C2T x TiO2 / Au powder was dispersed in anhydrous ethanol to prepare a dispersion, which was then drop-coated onto an Al2O3 substrate with multiple interdigitated electrodes. After drying, a sensitive film was formed on the interdigitated electrodes, thus preparing a Ti3C2T electrode. x / TiO2 / Au as a gas sensor with sensitive material;
[0080] A light source is placed above the gas sensor to emit light in the 530nm wavelength range towards the gas sensor during detection. The excitation of the external light source causes a plasmonic photothermal effect on the surface of the sensitive material, which reduces the activation energy of the surface reaction between the target gas molecules and the sensitive material. At the same time, the formed local high-temperature hot spot provides sufficient energy for the gas-sensitive reaction at room temperature, thereby enhancing the overall gas-sensitive performance of the gas sensor under room temperature operating conditions.
[0081] Combination Figure 2 As shown in Part A, in an optional implementation, Ti3C2T x The preparation process includes:
[0082] Step 1-1: Mix Ti3AlC2 powder with a mixture of LiF and HCl, and stir in a temperature-controlled water bath at 40°C for 48 hours.
[0083] Step 1-2: Centrifuge the mixture from Step 1-1 3-5 times with dilute hydrochloric acid to wash away any unreacted LiF.
[0084] Steps 1-3: Centrifuge the product from Step 1-2 multiple times with deionized water with a resistivity greater than 18.2 MΩ·cm until the pH reaches approximately 6 to eliminate residual LiF.
[0085] Steps 1-4: Wash and collect the precipitate obtained in steps 1-3, and vacuum dry it at 60°C for 12 hours to obtain Ti3C2T with a multi-layered structure. x .
[0086] In a preferred embodiment, in step 1-1, Ti3AlC2 powder, LiF and HCl solution are mixed in a ratio of 2g:2g:(38-42)mL, wherein the molar concentration of the HCl solution is 9M.
[0087] In another preferred embodiment, in steps 1-2, the molar concentration of the dilute hydrochloric acid is 2M.
[0088] Combination Figure 2 As shown in Part B, in an optional embodiment, the heterostructure of Ti3C2T x The preparation process of TiO2 includes:
[0089] Step 2-1: Prepare the Ti3C2T x Add to HCl solution and add NaBF4 as a crystal face control agent, stir for 30 minutes to make the solution uniformly dispersed;
[0090] Step 2-2: Transfer the mixture from Step 2-1 to a polytetrafluoroethylene hydrothermal reactor and oxidize it at 160°C for 3 hours.
[0091] Step 2-3: Cool the product from Step 2-2, then wash the precipitate 3-5 times with deionized water and anhydrous ethanol. Collect the precipitate by centrifugation and vacuum dry it at 60°C for 6 hours to obtain Ti3C2T with a heterostructure. x / TiO2.
[0092] In a preferred embodiment, Ti3C2T in step 2-1 x The ratio of HCl solution to NaBF4 solution is 25 mg:(3.8~4.2) mL:(3.8~4.2) mL, where the molar concentration of HCl is 1 M and the molar concentration of NaBF4 solution is 1 M.
[0093] Combination Figure 2 As shown in (Part C), in an optional embodiment, the heterostructure of Ti3C2T x The preparation process of / TiO2 / Au nanocomposite materials includes:
[0094] Step 3-1: The prepared Ti3C2T x / TiO2 and deionized water are added to a beaker and continuously oscillated in an ultrasonic instrument for 30 minutes until they are evenly dispersed;
[0095] Step 3-2: Add HAuCl4·3H2O to the mixture obtained in Step 3-1 and stir at 25°C for 4 hours;
[0096] Step 3-3: Centrifuge the solution obtained in Step 3-2 alternately with deionized water and anhydrous ethanol 3-5 times, then vacuum dry the precipitate at 60°C for 3 hours to obtain Ti3C2T. x / TiO2 / Au composite material.
[0097] In a preferred embodiment, Ti3C2T in step 3-1 x The ratio of TiO2 to deionized water is 5 mg:(0.8~1.2) mL.
[0098] In another preferred embodiment, in step 3-2, the molar concentration and volume of the HAuCl4·3H2O solution are determined based on the Au nanoparticles in Ti3C2T x The mass fraction of TiO2 / Au composite material is determined by Ti3C2T. x The preferred mass fraction of Au nanoparticles in the TiO2 / Au composite material is 1 wt.%.
[0099] In an optional implementation, the Ti3C2T x / TiO2 / Au exhibits a layered structure, with sheet-like TiO2 grown on its surface and Au nanoparticles freely distributed on the material surface and / or edges, forming a heterojunction at the material contact surface; the average size of the Au nanoparticles is 30-35 nm.
[0100] In an optional embodiment, the interdigitated electrode is an Ag-Pd electrode, employing 5 interdigitated electrodes, each with dimensions of 13.4mm*7mm*0.635mm, a linewidth of 0.2mm, and a spacing of 0.2mm; the substrate material is Al2O3 with dimensions of 6.8mm*3mm*0.5mm.
[0101] In an optional embodiment, the final sensitive membrane is formed by repeating the drop-coating and drying process 3 to 5 times during the preparation of the sensitive membrane.
[0102] In an optional embodiment, a gas sensor and a light source above the gas sensor are assembled in a housing, and the side of the housing is provided with a channel for gas to flow through.
[0103] In a preferred embodiment, the aforementioned gas sensor is fixedly disposed within the first cavity of the detection box;
[0104] A light source is installed in the second cavity of the detection box. During detection, the light source emits light with a wavelength range of 530nm to the sensor, which is Ti3C2T. x / TiO2 / Au provides a photo-assisted excitation environment.
[0105] Thus, Ti3C2T x A gas sensor made of TiO2 / Au as the sensitive material is placed in one part of the detection box, while a light source is fixed in the other part of the detection box. The detection box is powered by a built-in power supply or by an external power supply.
[0106] During detection, a 530nm light-assisted excitation environment is provided by a light source, which generates a plasmonic photothermal effect on the local surface of Au nanoparticles. The local hot spots drive the improvement of the gas sensor's gas-sensing performance and ensure the stability and consistency of the detection.
[0107] The implementation of the above preparation method will be described in more detail below with reference to specific embodiments.
[0108] Example 1
[0109] Multilayer Ti3C2T x Material preparation]
[0110] Step 1-1: Blend Ti3AlC2 powder (2g) with a mixture of LiF (2g) and HCl (9M, 40mL).
[0111] Steps 1-2: Stir in a temperature-controlled water bath at 40℃ for 48 hours.
[0112] Steps 1-3: Wash the unreacted LiF by centrifuging 5 times with dilute hydrochloric acid (2M HCl).
[0113] Steps 1-4: Centrifuge with deionized water (resistivity greater than 18.2 MΩ·cm) 5 times until the pH reaches about 6 to eliminate residual LiF.
[0114] Steps 1-5: Wash the precipitate, collect it, and vacuum dry it at 60°C for 12 hours to obtain Ti3C2T. x The material was used to obtain a sample, which was named MT0.
[0115] Among them, Ti3C2T x The material exhibits a layered accordion-like structure.
[0116] Example 2
[0117] [Heterogeneous Ti3C2T] x Preparation of TiO2 nanocomposites
[0118] Step 2-1: Add MTO (100 mg) to HCl solution (1 M, 16 mL) and add NaBF4 (0.1 M, 16 mL) as a crystal facet control agent.
[0119] Step 2-2: Stir for 30 minutes to ensure the solution is evenly dispersed.
[0120] Steps 2-3: Transfer the mixture to a polytetrafluoroethylene hydrothermal reactor and oxidize it at 160°C for 3 hours.
[0121] Steps 2-4: After cooling, wash the precipitate five times with deionized water and anhydrous ethanol.
[0122] Steps 2-5: Collect the samples by centrifugation and vacuum dry them at 60°C for 6 hours. Name the collected samples MT3.
[0123] Example 3
[0124] [Heterogeneous Ti3C2T] x Preparation of TiO2 / Au nanocomposite materials]
[0125] Step 3-1: After continuous oscillation in an ultrasonic instrument for 30 minutes, add 100mg of the prepared MT3 sample and 20mL of deionized water to a beaker and disperse evenly.
[0126] Step 3-2: Add HAuCl4·3H2O (100mM, 0.065ml) to the above mixture and stir at 25°C for 4 hours.
[0127] Step 3-3: Centrifuge the resulting solution alternately with deionized water and anhydrous ethanol 5 times.
[0128] Steps 3-4: Vacuum dry at 60℃ for 3 hours to obtain Ti3C2T x The TiO2 / Au composite material is named MTA.
[0129] Example 4
[0130] [Preparation of the Sensing Layer for an NO2 Gas Sensor]
[0131] Step 4-1: Disperse 0.02g of MTA gas-sensitive material evenly in 1mL of anhydrous ethanol, and then sonicate for 20 minutes to obtain a uniformly dispersed suspension.
[0132] Step 4-2: Drop 2 μL of dispersion onto an Al2O3 substrate (6.8 mm × 3 mm × 0.5 mm) with interdigitated electrodes of 5 Ag / Pd, and dry at 60 °C for 30 min to prepare a sensitive film layer.
[0133] During the preparation process, the drop coating and drying processes were repeated 5 times.
[0134] The electrodes are commercially available electrodes purchased directly, and the spacing between the cross values is 200 micrometers.
[0135] The materials used in the following tests are all from Examples 1-4.
[0136] Microstructure testing
[0137] like Figure 3 As shown, the XRD patterns reveal the crystal phase information of MT0, MT3, and MTA for the original Ti3C2T. x (i.e., MTO), the typical diffraction peaks are consistent with the crystal plane characteristics in the standard spectrum, confirming the successful synthesis of MTO; in addition, four characteristic peaks of Au (JCPDS No. 040784) can be seen in the MTA sample, and except for Ti3C2T x No other impurity components were found besides the diffraction peaks of TiO2, indicating that Ti3C2T was successfully formed. x / TiO2 / Au complex.
[0138] Figure 4 a is the surface morphology of MT3, compared to MT0 ( Figure 4 b) Its surface is rougher, indicating that the square TiO2 nanosheets are in Ti3C2Tx It has grown successfully.
[0139] Figure 5 This is a surface morphology diagram of MTA, in which Ti3C2T x The nanosheets are uniformly modified with TiO2 nanosheets (yellow box) and Au nanoparticles (red circle); combined with Figure 6 It is known that Au nanoparticles with an average size of 30–35 nm are randomly distributed throughout the Ti3C2T matrix. x There is no obvious aggregation on the surface or edge of the / TiO2 composite material.
[0140] Figure 7 The EDS plot of the medium MTA reveals the spatial distribution of Ti, C, O and Au elements. The elemental distribution in the figure can further verify the uniform distribution of TiO2 and Au nanoparticles.
[0141] Figure 8 This is a TEM image of the MTA, showing Ti3C2T. x It exhibits a sheet-like morphology and serves as a substrate for the growth of TiO2 nanosheets and Au nanoparticles.
[0142] The characterization methods described above demonstrate that this invention successfully prepared Ti3C2T. x / TiO2 / Au.
[0143] XPS spectral and optical characterization of MT3 and MTA
[0144] Figure 9 The XPS spectra of MT3 and MTA were measured, and the wide-scan XPS spectra showed the corresponding constituent elements of MT3 and MTA, respectively.
[0145] Compared with pure Ti3C2T x and Ti3C2T x Compared to TiO2, Ti3C2T x The / TiO2 / Au spectrum contains additional Au elements besides Ti, C, and O, which perfectly matches the EDS results. Furthermore, the presence of F is likely primarily due to the introduction of -F functional groups during the etching process, and no significant Al peak was observed, confirming successful Al removal from Ti3AlC2.
[0146] Figure 10 , Figure 11 and Figure 12These are high-resolution XPS spectra of Ti 2p, O 1s, and C 1s. The binding energies of the Ti 2p3 / 2 core levels at 455 eV, 455.7 eV, 457.2 eV, and 459.4 eV in the MT3 sample can be attributed to Ti-C bonds, Ti-X bonds from substoichiometric TiCx (x < 1) or titanium carbide, and reduced Ti ions (Ti... x O y ) and 4 + Ti ions (TiO2).
[0147] The O 1s core energy level can be decomposed into four characteristic peaks centered at 529.6, 530.5, 532.1, and 533.1 eV, originating from surface-adsorbed oxygen species (Oads), lattice oxygen in TiO2 (Ti-O-Ti), Ti-OH, and C-OH bonds, respectively, indicating the presence of numerous oxygen-containing functional groups. The C 1s core energy level is divided into six Gaussian fitted peaks centered at 281.8, 282.7, 283.8, 284.8, 286.2, and 288.3 eV, corresponding to Ti-C, C-Ti-Oa, C-Ti-Ob, CC, CO, and CF bonds, respectively. After Au nanoparticle modification, a slight shift towards lower binding energies (approximately 0.3 eV) can be observed in the MTA plots of Ti 2p, O 1s, and C 1s, confirming the presence of interfacial charge transfer and Ti3C2T. x The formation of heterostructures between TiO2 and Au.
[0148] Figure 13 High-resolution XPS images of Au 4f in the MTA sample are shown, revealing two characteristic peaks at 83.7 and 87.3 eV, which are attributed to Au 4f 7 / 2 and Au 4f 5 / 2 in metallic Au, respectively. This indicates the successful synthesis of Au nanoparticles and Ti3C2T x Au nanoparticles were successfully loaded onto TiO2.
[0149] Figure 14 The images show the UV-Vis absorption spectra of MT3 and MTA. No specific absorption peaks were observed in the MT3 sample across the entire visible light range. After modification with Au nanoparticles, the absorption of MTA in the visible light range was significantly improved, and it exhibited an additional absorption peak near 530 nm. This may be attributed to the LSPR effect induced by the introduction of appropriate Au nanoparticles.
[0150] The above tests demonstrate that the Ti3C2T prepared by this invention... x The elemental composition of / TiO2 / Au is such that no other impurities or substances are generated.
[0151] The microstructure tests, XPS spectroscopy, and optical characterization described above demonstrate that this invention successfully prepared Ti3C2T with a heterostructure. x / TiO2 / Au nanomaterials.
[0152] MT3 gas-sensing performance tests under different NO2 concentrations and different light irradiation conditions
[0153] Figure 15 This is the dynamic response curve of the MT3 sensor to NO2 concentrations ranging from 1 to 50 ppm over time.
[0154] The MT3 gas sensor exhibited relatively clear response / recovery behavior across the entire test range, demonstrating repeatability for continuous measurements at 1 ppm NO2 and dynamic response performance across a concentration range of 1 to 50 ppm NO2. However, it still suffers from slow response recovery and incomplete recovery, a common problem encountered with gas sensitivity at room temperature, primarily due to insufficient activation energy of the effective gas reaction within the system.
[0155] Figure 16 The figures show the response and recovery curves of the MT3 sensor to 5 ppm NO2 under different light fields (i.e., in the absence of light, 365 nm, 420 nm, 495 nm, 530 nm, and 620 nm). The results indicate that the response / recovery behavior of the MT3 gas sensor remains almost consistent under various illumination conditions, with no significant change in response value. This means that the additional light field cannot effectively improve the response of Ti3C2T. x Gas-sensitive response of TiO2 composite materials.
[0156] MTA gas-sensing performance tests on NO2 concentrations under different light irradiation and 530nm light irradiation.
[0157] Figure 17 The effects of Au nanoparticles on Ti3C2T under different wavelengths of light irradiation were analyzed. x The effect of TiO2 gas-sensing performance (i.e., 365nm, 420nm, 495nm, 530nm, and 620nm in the absence of light). The results show that the MTA sensor has the largest light response at a wavelength of 530nm, which is due to the effect of Ti3C2T. x The / TiO2 / Au nanocomposite exhibits strong absorption around 530 nm.
[0158] Figure 18 The dynamic response / recovery curves of the MTA-530 sensor (an MTA gas sensor illuminated by 530 nm light) to 1-50 ppm NO2 were analyzed. It can be seen that, compared with the MT3 gas sensor, the MTA-530 sensor exhibits superior and recoverable response and recovery behavior, confirming its repeatability and reversibility.
[0159] Further testing was conducted on the gradient response curves of NO2 from 1 ppm to 50 ppm. Compared with the MT3 gas sensor, the MTA-530 sensor exhibited a significantly enhanced response and strong response / recovery sensing characteristics throughout the entire tested concentration range.
[0160] As shown above, due to the unique LSPR effect of the MTA-530 sensor, Au nanoparticles exhibit significant optical resonant absorption, which significantly enhances the light absorption capability of the sensitive material. In particular, high-energy hot electrons induced by plasmon relaxation can be effectively transferred into the metal lattice through electron-electron and electron-phonon scattering mechanisms, resulting in instantaneous localized high temperatures. This is expected to provide additional activation energy for the gas-sensitive reaction, further enhancing its gas-sensitive properties.
[0161] Therefore, Au nanoparticles can be used as light absorption amplifiers to realize the effect of light-irradiated Ti3C2T x / Improved gas-sensing performance of TiO2 gas sensor.
[0162] Comparison of gas sensing performance of MT3, MTA, and MTA-530 gas sensors
[0163] Figure 19 The correlation between the response values of MT3, MTA, and MTA-530 sensors and NO2 concentration was analyzed.
[0164] The linear fitting curve clearly shows that the MTA-530 sensor exhibits the highest sensitivity, at 4.2% ppm. -1 (Determined by the slope of the fitted curve), which is 16.15 times and 4.12 times that of the MT3 and MTA gas sensors, respectively. Furthermore, the MTA-530 sensor exhibits good linearity across the entire NO2 concentration range (1-50 ppm), demonstrating its potential to distinguish different NO2 concentrations over a longer range.
[0165] Figure 20 Histograms comparing the selectivity of the MT3, MTA, and MTA-530 sensors for different gases were analyzed. The gases included 50 ppm NO2 and 100 ppm interfering gases (i.e., NH3, HCHO, CH3COCH3, C2H5OH, and CH3OH). It was clearly observed that the MTA-530 sensor exhibited the highest response to 50 ppm NO2, indicating that the selectivity was improved by utilizing Au nanoparticle modification and light irradiation of the device.
[0166] Figure 21The radar plots of various gas-sensing performance parameters for NO2 by the MT3, MTA, and MTA-530 sensors were analyzed, including recoverability, responsivity, recovery rate, response value, sensitivity, and selectivity. A larger coverage area indicates better gas-sensing performance. The plots clearly show that the MTA-530 sensor has a larger coverage area (yellow area) than the other two gas sensors, confirming its superior gas-sensing performance across various metrics, including favorable recoverability, excellent selectivity, response / recovery rate, optimal response value, and sensitivity.
[0167] Figure 22 This study analyzes and studies the moisture resistance and long-term stability of sensor devices.
[0168] for Figure 22 a. The response characteristics of the MTA-530 sensor to 10 ppm NO2 gas under different relative humidity (RH) conditions were studied within the range of 10%–90%, and the effect of ambient humidity on the gas-sensing performance of the sensor was investigated. It was observed that the response value of the MTA-530 sensor exhibited slight changes under common humidity conditions from 30% RH to 70% RH. The response value of the MTA-530 sensor gradually increased with increasing relative humidity. This is due to the increased hydroxyl site density, which accelerates the adsorption of NO2 gas and amplifies the sensitive response, indicating that the MTA-530 sensor has potential for applications in high humidity environments.
[0169] exist Figure 22 As can be seen in section b, the stability of the MTA-530 sensor was evaluated by testing its response to 1 ppm NO2 and resistance fluctuation over a 16-day period. The results showed no significant fluctuations in resistance and response values, with relative standard deviations (RSDs) as low as 0.65 and 0.09, respectively, indicating that the MTA-530 sensor of this invention has good long-term stability.
[0170] Light-assisted 530nm heterostructure Ti3C2T x / TiO2 / Au plasmonic photothermal NO2 sensing mechanism
[0171] Figure 23 The electric field distributions of MT3 and MTA were calculated using the finite-difference time-domain (FDTD) numerical simulation method. Analysis revealed that due to the localized plasmon resonance (LSPR) effect of Au nanoparticles, a significant electric field enhancement was generated on the MTA surface at the local nanoscale around the Au nanoparticles, exhibiting a maximum normalized electric field intensity (|E / E0|). 2 𝑚𝑎𝑥 The electric field strength reaches 428.5, significantly higher than MT3's 2.9. This increased electric field will significantly enhance the light absorption efficiency. Utilizing the maximum amplification of the local electric field strength and the amplification of light absorption efficiency, Ti3C2T... x / TiO2 / Au gas-sensitive materials can effectively modulate and increase the number of high-energy photoactivated charge carriers. During the subsequent relaxation process, these photoactivated high-energy electrons are effectively converted into thermal energy, resulting in high temperatures around local hot spots.
[0172] Therefore, in the gas sensor of the present invention, the plasmon photothermal effect of Au nanoparticles provides additional activation energy, as does Ti3C2T x The matching of the absorption spectrum and excitation wavelength of the / TiO2 / Au composite material effectively improves the light absorption efficiency, which is the main reason for the improved gas sensitivity under 530nm light.
[0173] To further reveal the existence of plasmon photothermal effect Figure 24 The temperature changes of the MT3 and MTA sensors before and after irradiation with 530nm light were recorded at 200s intervals using an infrared thermal imager.
[0174] The surface temperature of the MTA sensor increased from 27.9 °C to 30.2 °C, an increase of 2.3 °C, while the surface temperature of the MT3 sensor showed a correspondingly small increase of only about 0.4 °C. The higher temperature rise on the MTA sensor surface can be attributed to the plasmon photothermal effect induced by the introduction of Au nanoparticles. Although the overall temperature rise on the sensitive material surface is not high, this is only a macroscopic temperature generated by a collective localized photothermal effect. In fact, the plasmon photothermal effect can generate instantaneous high temperatures on the nanoscale surface near metal nanoparticles and provide sufficient activation energy to promote the interaction of gas molecules with Ti3C2T. x Gas-sensitive reaction of the / TiO2 / Au composite system.
[0175] Figure 25 and 26 These are schematic diagrams illustrating the NO2 sensing mechanism of the MTA-530 gas sensor under no light irradiation and with 530nm light irradiation.
[0176] Depend on Figure 25 When the MTA sensor is exposed to ambient air without light, oxygen molecules (O2) 2(gas) It tends to target the surface of sensitive materials and then traps electrons from the conduction band of the sensitive material. When transitioning to a NO2 atmosphere, due to the strong oxidizing power of NO2, the adsorbed NO2 molecules (NO... 2(gas) It can not only directly capture electrons from the surface of sensitive materials Furthermore, it will react with oxygen chemically adsorbed on the surface. Interaction occurs, producing
[0177] The aforementioned reaction process continuously consumes electrons, thus decreasing conductivity and increasing resistance, thereby exhibiting a positive response to NO2 gas. However, due to insufficient activation energy at room temperature, an inadequate gas-sensitive response occurs on the MTA sensor, resulting in weak sensitivity and slow response / recovery speed.
[0178] After irradiation with 530 nm light, thanks to the optimal match between the excitation wavelength and the absorption band, and the enhanced electric field triggered by the LSPR effect of Au nanoparticles, photogenerated charge carriers (i.e., photogenerated charge carriers) via additional channels of electronic transitions (i.e., photogenerated charge carriers) are generated. The number of ) has increased dramatically. This includes plasmon-activated carrier generation (PCT) and plasmon-induced interfacial charge transfer transitions (PICTT). The increased photogenerated electrons not only promote the adsorption of O2 and NO2 molecules on the surface of sensitive materials, but also... Moreover, it greatly accelerates the gas-sensitive reaction process, which is beneficial to improving the response performance of the gas-sensitive element under 530nm light irradiation.
[0179] Besides the effect of photogenerated electrons, photo-excited holes are another reason for improved gas-sensing properties. When the gas-sensing device returns to the ambient air, the photo-excited holes can participate in the adsorption of NO2. - Reactions of substances It accelerates the desorption of NO2 molecules, thus exhibiting faster recovery behavior compared to dark conditions.
[0180] Furthermore, due to electron-electron interactions and collisions, plasmon resonance relaxation generates a large number of high-energy hot carriers (i.e., plasmon-induced hot electrons). Plasmon-induced thermal holes The high energy of hot carriers can be transferred directly or indirectly to sensitive reaction sites, which will introduce additional excited reaction pathways: This further enhances the sensor's response characteristics. In particular, subsequent electron-phonon and phonon-phonon interactions will induce lattice thermal effects and provide localized heating for Au nanoparticles.
[0181] Plasmon photothermal effect not only reduces the activation energy of the surface reaction between the target gas molecules and the sensitive material, but also provides sufficient energy by increasing the local temperature around the active site, thereby accelerating the gas-sensing reaction process mentioned above, and ultimately helping to enhance the overall gas-sensing performance of MXene-based sensors under room temperature operating conditions.
[0182] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor, characterized in that, The gas sensor comprises an Al2O3 substrate with multiple interdigitations and a sensitive material on the interdigitated electrodes. A light source is disposed above the gas sensor, and the center wavelength of the light source is 530 nm to provide a light-assisted excitation environment. The sensitive material is Ti3C2T with a heterostructure. x The / TiO2 / Au nanocomposite material generates a plasmonic photothermal effect in the sensitive material system through excitation by an external light source, which reduces the activation energy of the system reaction between the target gas molecules and the sensitive material. At the same time, the formed local high-temperature hot spots provide sufficient energy for the gas-sensitive reaction at room temperature, thereby enhancing the overall gas-sensitive performance of the gas sensor under room temperature operating conditions.
2. The plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor according to claim 1, characterized in that, Ti3C2T x / TiO2 / Au nanocomposites include Ti3C2T exhibiting a multilayered structure. x And the lamellar TiO2 grown on its surface constitutes Ti3C2T with a heterostructure. x / TiO2 composite material, in the Ti3C2T x Au nanoparticles are freely distributed on the surface and / or edges of the TiO2 composite material, and the Au nanoparticles are related to Ti3C2T x The contact interface of the / TiO2 composite material forms a heterojunction.
3. The plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor according to claim 2, characterized in that, The average size of Au nanoparticles is 30~35 nm.
4. A method for preparing a plasmonic photothermal driven MXene-based room-temperature high-sensitivity NO2 gas sensor according to any one of claims 1-3, characterized in that, Includes the following steps: Preparation of Ti3C2T x The prepared Ti3C2T x It exhibits a multi-layered structure; In Ti3C2T x Ti3C2T with a heterostructure is obtained by growing lamellar TiO2 on the surface. x / TiO2 composite material; Au nanoparticles were loaded onto Ti3C2T x Au nanoparticles on TiO2 and Ti3C2T x The contact interface of the TiO2 composite material forms a heterojunction, resulting in Ti3C2T with a heterostructure. x / TiO2 / Au nanocomposite materials; With heterostructure Ti3C2T x The preparation of gas sensors using TiO2 / Au as the sensing material specifically includes: using Ti3C2T x TiO2 / Au powder was dispersed in anhydrous ethanol to prepare a dispersion, which was then drop-coated onto an Al2O3 substrate with multiple interdigitated electrodes. After drying, a sensitive film was formed on the interdigitated electrodes, thus preparing a Ti3C2T electrode. x / TiO2 / Au as a gas sensor with sensitive material; A light source is placed above the gas sensor to emit light in the 530 nm wavelength range towards the gas sensor during detection. The excitation of the external light source causes a plasmonic photothermal effect on the surface of the sensitive material, which reduces the activation energy of the surface reaction between the target gas molecules and the sensitive material. At the same time, the formed local high-temperature hot spot provides sufficient energy for the gas-sensitive reaction at room temperature, thereby enhancing the overall gas-sensitive performance of the gas sensor under room temperature operating conditions.
5. The method according to claim 4, characterized in that, Ti3C2T x The preparation process includes: Step 1-1: Mix Ti3AlC2 powder with a mixture of LiF and HCl, and stir in a temperature-controlled water bath at 40°C for 48 hours. Step 1-2: Use dilute hydrochloric acid to centrifuge the mixture from Step 1-1 several times to wash away any unreacted LiF. Steps 1-3: Centrifuge the centrifuged product from Step 1-2 multiple times with deionized water with a resistivity greater than 18.2 MΩ·cm to eliminate residual LiF. Steps 1-4: Wash and collect the precipitate obtained in steps 1-3, and vacuum dry it to obtain Ti3C2T with a multi-layered structure. x .
6. The method according to claim 4, characterized in that, Heterogeneous Ti3C2T x The preparation process of TiO2 includes: Step 2-1: Prepare the Ti3C2T x Add it to the HCl solution, and add NaBF4 as a crystal facet control agent. Stir to make the solution evenly dispersed. Step 2-2: Transfer the mixture from Step 2-1 to a polytetrafluoroethylene hydrothermal reactor and oxidize it at 160°C for 3 hours. Step 2-3: Cool the product from Step 2-2, then wash the precipitate 3-5 times with deionized water and anhydrous ethanol. Collect the precipitate by centrifugation and vacuum dry to obtain Ti3C2T with a heterostructure. x / TiO2.
7. The method according to claim 4, characterized in that, Heterogeneous Ti3C2T x The preparation process of / TiO2 / Au nanocomposite materials includes: Step 3-1: The prepared Ti3C2T x / TiO2 and deionized water are added to a beaker and continuously oscillated in an ultrasonic instrument until they are evenly dispersed; Step 3-2: Add HAuCl4⋅3H2O to the mixture obtained in Step 3-1 and stir at 25°C for 4 hours; Step 3-3: Centrifuge the solution obtained in Step 3-2 alternately with deionized water and anhydrous ethanol 3-5 times, then vacuum dry the precipitate to obtain Ti3C2T. x / TiO2 / Au composite material.
8. The method according to claim 4, characterized in that, The Ti3C2T x / TiO2 / Au exhibits a multi-layered structure with sheet-like TiO2 grown on its surface and Au nanoparticles freely distributed on the material surface and / or edges, forming a heterojunction at the material contact surface; the average size of the Au nanoparticles is 30~35 nm.
9. The method according to claim 4, characterized in that, The interdigitated electrodes are Ag-Pd electrodes, the substrate material is Al2O3, the linewidth is 0.2 mm, and the spacing is 0.2 mm.
10. The preparation method according to claim 4, characterized in that, In the process of preparing the sensitive membrane, the final sensitive membrane is formed by repeating the drop coating and drying process 3 to 5 times.
Citation Information
Patent Citations
Gas sensor and preparation method thereof
CN103698365A
Room temperature NO2 gas sensor based on MoS2-PbS composite materials and preparation method thereof
CN108680610A
